COVID-19: Nationalism and global solidarities - Fadhila Inas Pratiwi; Ahalla Tsauro (Faculty of Social and Political Science, Universitas Airlangga, 2021)
As the COVID-19 crisis emerged, many forms of nationalism have been rising, such as racism, state individualism, vaccine nationalism, and so forth. However, this kind of nationalism cannot solve the global pandemic that affects various aspects of human life that needs global solidarity in the framework of thinking. The purpose of this article is to explore the relationship between COVID-19, nationalism, and global solidarity. This article used the literature review method to compare and contrast the COVID-19, Nationalism, and Global Solidarity arguments by using reputable resources such as journals, research reports, and news articles. This article was divided into three sections: 1) the explanation about nationalism, its definition, and theoretical approach, 2) state and nationalism in crisis time, 3) cooperation and global solidarity. It concluded that the COVID-19 period showed us people tend to have greater individuality and higher attachment to their groups and state, as Social Identity Theory (SIT) suggests. It manifested in state nationalist view that state as the sole player in mitigating this pandemic shows selfish attitude. However, as the COVID-19 served as a global pandemic, it also needs global solidarity which has been proven in solving the spread of coronavirus and tackle its impact.